2017
DOI: 10.1016/j.mcna.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Anemia of Inflammation

Abstract: Impaired iron homeostasis and the suppressive effects of proinflammatory cytokines on erythropoiesis, together with alterations of the erythrocyte membrane that impair its survival, cause the anemia of inflammation. Recent epidemiologic studies have connected inflammatory anemia with critical illness, obesity, aging, and kidney failure, as well as with cancer, chronic infection, and autoimmune disease. The proinflammatory cytokine, interleukin-6, the iron regulatory hormone, hepcidin, and the iron exporter, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(113 citation statements)
references
References 71 publications
0
107
0
6
Order By: Relevance
“…Aging has long been regarded as a contributor to infections on the basis of immunosenescence [40]. However, whether anaemia actually causes increased nosocomial infection or it is merely an additional marker of inflammation [41,42] and malnutrition [43] requires further study. In contrast to previous study [9][10][11][12][13], no comorbidities were confirmed as risk factors of nosocomial infection in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Aging has long been regarded as a contributor to infections on the basis of immunosenescence [40]. However, whether anaemia actually causes increased nosocomial infection or it is merely an additional marker of inflammation [41,42] and malnutrition [43] requires further study. In contrast to previous study [9][10][11][12][13], no comorbidities were confirmed as risk factors of nosocomial infection in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The most common form is iron deficiency anemia, with absolute iron deficiency anemia the easiest to diagnose and treat . The second most common is anemia of inflammation (formerly referred to as anemia of chronic disease), which can result from either acute or chronic inflammatory conditions . Cessation of cigarette smoking, which is likely to happen with hospital admission, has also been reported to result in an acute decrease in a patient's measured Hb level …”
Section: Discussionmentioning
confidence: 99%
“…Preoperative low hemoglobin levels can lead to tumor hypoxia, which promotes tumor growth by stimulating angiogenesis, acquiring genome mutations, and increasing resistance to apoptosis [13,29] and further leads to increased staging and a poor prognosis. On the other hand, it is speculated that tumor-related inflammation may result in the release of various inflammatory factors, which may affect erythropoietin synthesis and lead to the decrease in HGB [30]. Currently, hemoglobin is not commonly used in various risk prediction tools, so the results of this study suggest that we need to improve our understanding of the impact of preoperative anemia or low hemoglobin levels on postoperative survival.…”
Section: Discussionmentioning
confidence: 93%